Normal Liver Size In Adults Without Suspicion Of Liver Disease Analyzing The Variable (Age, Weight, & Height) That Has Good Correlation - Rashid, Ali; Ali, Abid; zulfiqar, Taiba (Medical Science Journal for Advance Research, 2022)
Aim/Objective:To determine the normal liver size in adults without suspicion of liver disease analyzing the variable (age, weight, & height) that has good correlation. Methods: The study was undertaken in Department of Radiology in Services Hospital (SHL)/ Services Institute of Medical Sciences (SIMS) Lahore. It was hospital based study and normal healthy adult without liver disease in the age range from 18 years to 78 years were selected for this study. 207 healthy adults without liver disease & without specification of gender were selected. Non- randomized or consecutive sampling technique was used due to limited time of 3 months from 1st December 2016 to 1st March 2016. Results: The mean age of total subjects was 34.85±14.67 years. The mean age of male was 35.6± 14.47 years and 33.8±14.95 years for female. There were 83 (40%) subjects in the age range of 18-27 years, 51 (24.6%) subjects in the age range of 28-37 years, 29 (14.1%) subjects in the age range of 38-47 years, 24 (11.6%) subjects in the age range of 48-57 years, 13 (6.3%) subjects in the age range of 58-67 years, 7 (3.4%) subjects in the age range of 68-77 years.The mean longitudinal diameter of liver of total subjects was 14.34±0.79cm (p=0.001). The mean longitudinal diameter of liver was 14.50±0.71cm & 14.1±0.84cm in male and female respectively. The mean height of total subjects was 163.56±6.7cm. The mean height was 165.74±6.0cm for male & 160.72±6.6 for female respectively. The distribution of liver sizes in the various age groups is shown in table 3. The result demonstrates that liver sizes increases with age. The results also show that males had larger liver size than females. The size of the liver was correlated with age, weight, and height showed positive and significant correlation with liver size. Conclusion:Ultrasound has been found to be both accurate and wide spread in clinical use and has no proven health hazard. The sonographic measurement of liver at the midclavicular line was shown to be an easy and practical method for routine use. Sex and body height are the most important factors associated with the diameter of the liver measured at the midclavicular line.